2013
DOI: 10.1093/jxb/ert430
|View full text |Cite
|
Sign up to set email alerts
|

ROS homeostasis in halophytes in the context of salinity stress tolerance

Abstract: Halophytes are defined as plants that are adapted to live in soils containing high concentrations of salt and benefiting from it, and thus represent an ideal model to understand complex physiological and genetic mechanisms of salinity stress tolerance. It is also known that oxidative stress signalling and reactive oxygen species (ROS) detoxification are both essential components of salinity stress tolerance mechanisms. This paper comprehensively reviews the differences in ROS homeostasis between halophytes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
524
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 782 publications
(556 citation statements)
references
References 166 publications
28
524
1
3
Order By: Relevance
“…Previous research supports our findings that supplementation of optimal mineral concentrations keeps ROS at nontoxic levels (Ahanger et al 2015;Iqbal et al 2015). SOD acts on superoxide radicals, which are further scavenged by either CAT or APX through the ascorbate-glutathione pathway; as a result, superoxide radicals are removed and prevented from forming more toxic radicals (Ahmad et al 2010;Bose et al 2014). Additionally, SOD prevents metal-mediated formation of toxic OH − .…”
Section: Discussionsupporting
confidence: 88%
“…Previous research supports our findings that supplementation of optimal mineral concentrations keeps ROS at nontoxic levels (Ahanger et al 2015;Iqbal et al 2015). SOD acts on superoxide radicals, which are further scavenged by either CAT or APX through the ascorbate-glutathione pathway; as a result, superoxide radicals are removed and prevented from forming more toxic radicals (Ahmad et al 2010;Bose et al 2014). Additionally, SOD prevents metal-mediated formation of toxic OH − .…”
Section: Discussionsupporting
confidence: 88%
“…The higher SOD activity observed in A/A25 plants under salinity, leading to H 2 O 2 production, could be the signal triggering the cascade of adaptive (genetic and physiological) responses (Bose et al, 2014, Rejeb et al, 2015. Recently, several researches have indicated that proline accumulation occurs in stressed plants and can be mediated by signaling molecules, including H 2 O 2 (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…/K ? ratio disrupt ion homeostasis and decrease other nutrient uptake (Simaei et al 2012;Bose et al 2014;Rahman et al 2016a). In the present study, salt stress increased Na ?…”
Section: Discussionmentioning
confidence: 99%